Service quality and user satisfaction of the reader's advisory desk service : a case study of University Putra Malaysia Library / Zubaidah Iberahim and Fuziah Mohd Nadzar - Iberahim, Zubaidah; Mohd Nadzar, Fuziah (Faculty of Information Management, 2011)
This study identified what the users of the UPM library perceive to be the quality of the Reader's Advisory Desk Service, to establish the extent to which the reader advisor meets the users' satisfaction of the services provided, and to investigate the quality of the Reader's Advisory Desk Service and its relationship with satisfaction. This study was done in UPM library and 40 respondents were selected. SERVQUAL questionnaires were distributed as the research for the data gathering. Purposive sampling/judgment sampling was the sampling technique chosen to determine the size of respondents selected. Purposive sampling was chosen because it represents only the respondents who posed questions and problems to the Reader's Advisory Desk Service of the UPM Library or the respondents who have been identified as a frequent users of the Reader's Advisory Desk Service. Thereby, it is confined to the specific types of respondents or specific target groups who can provide the desired information. Overall, majority of the users were satisfied with Reader's Advisory Desk service offered based on the service parameters of "tangibles, responsiveness, reliability, assurance and empathy of service." Arising from these results, this study revealed that there is significant positive relationship between the effectiveness of the Reader's Advisory Desk service and users' satisfaction; and by further improving the quality of the service; it will lead to users' needs being met and their level of satisfaction being fulfilled. This study systematically examined a reference activity which is the effectiveness of Reader's Advisory Desk service views on the nature and practice in UPM library specifically.